1993
DOI: 10.1007/bf01295721
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bile diversion does not alter canine interdigestive myoelectric activity

Abstract: Previous studies have suggested that the cyclic entry of bile into the duodenum during fasting regulates interdigestive patterns of motility by releasing the putative regulatory hormone motilin. Our aim was to determine if cyclic secretion of bile into the duodenum regulates interdigestive myoelectric activity and plasma motilin concentrations. Six dogs were prepared with gastric and intestinal serosal electrodes. Myoelectric activity was measured during fasting and after a meal before and after reoperative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…Nevertheless, controversial results have been reported on the relationship of phase III and gall bladder contraction in the interdigestive state. 30 Also, in the present study, no effects of intraduodenal bile salt infusions on MMC cycle length were found (table 1). The mechanism of the negative feedback control in the fasting state deserves further comment.…”
Section: Discussioncontrasting
confidence: 46%
“…Nevertheless, controversial results have been reported on the relationship of phase III and gall bladder contraction in the interdigestive state. 30 Also, in the present study, no effects of intraduodenal bile salt infusions on MMC cycle length were found (table 1). The mechanism of the negative feedback control in the fasting state deserves further comment.…”
Section: Discussioncontrasting
confidence: 46%
“…Nevertheless, controversial results have been reported on the relationship of phase III occurrence and intestinal bile salts in the interdigestive state. After biliary diversion in dogs, some investigators have reported unchanged MMC cycling, 14 whereas others reported a loss of MMCs. 13,15 In humans, two previous studies from our group found no effects of intraduodenal bile salt infusions on timing of the various phases of the MMC.…”
Section: Discussionmentioning
confidence: 99%
“…The former studies argue that an intact enterohepatic circulation is essential for normal MMC cycling, with initiation of normal MMCs by bile acid stimulation of putative receptors existing between the portal vein and intrahepatic bile ducts. Bile should then not even be necessary in the duodenum for regulation of the MMC [13, 34]. Another role of bile may be that of an excitatory modulator that decreases the relative refractory period of the gastrointestinal MMC for other stimuli like motilin, thereby increasing the rate of MMC cycling [8].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rats and dogs showed that bile diversion disturbs the normal MMC, and subsequent intraduodenal infusion of bile acids or bile restores the MMC pattern [8, 9, 10, 11]. In contrast, some other studies report no changes in the MMC after chronic bile diversion [12, 13]. In humans, a close association between inter-digestive gallbladder motility and gastroduodenal motility is found [4, 5].…”
Section: Introductionmentioning
confidence: 99%